Duration effect of desflurane anesthesia and its awakening time and arterial concentration in gynecologic patients (Clinics, 2013)
OBJECTIVES: To determine the awakening arterial blood concentration of desflurane and its relationship with the end-tidal concentration during emergence from various durations of general anesthesia. METHOD: In total, 42 American Society of Anesthesiologists physical status class I-II female patients undergoing elective gynecologic surgery were enrolled. General anesthesia was maintained with fixed 6% inspiratory desflurane in 6 l min-1 oxygen until shutoff of the vaporizer at the end of surgery. One milliliter of arterial blood was obtained for desflurane concentration determination by gas chromatography at 20 and 10 minutes before and 0, 5, 10, 15, and 20 minutes after the discontinuation of desflurane and at the time of eye opening upon verbal command, defined as awakening. Concentrations of inspiratory and end-tidal desflurane were simultaneously detected by an infrared analyzer. RESULTS: The mean arterial blood concentration of desflurane was 1.20% at awakening, which correlated with the awakening end-tidal concentration of 0.96%. The mean time from the discontinuation of desflurane to eye opening was 5.2 minutes (SD = 1.6, range 3-10), which was not associated with the duration of anesthesia (60-256 minutes), total fentanyl dose, or body mass index (BMI). CONCLUSIONS: The mean awakening arterial blood concentration of desflurane was 1.20%. The time to awakening was independent of anesthetic duration within four hours. Using well-assisted ventilation, the end-tidal concentration of desflurane was proven to represent the arterial blood concentration during elimination and could be a clinically feasible predictor of emergence from general anesthesia.